Nanoparticle composition with reduced foreign matter and method for producing same

By controlling the pH of the slurry during pulverization with specific dispersion media, the method effectively reduces impurities in bead mill processes, ensuring high-purity refined particles for electronic components and pharmaceuticals.

JP7602997B2Active Publication Date: 2024-12-19SHIONOGI & CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021504065
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-01
Filing Date
2020-02-28
Publication Date
2024-12-19
Estimated Expiration
2040-02-28

AI Technical Summary

Technical Problem

Contamination during the pulverization process using a bead mill leads to adverse effects in high-purity materials for electronic components and pharmaceuticals, necessitating a solution to reduce impurities.

Method used

The method involves controlling the pH of the slurry during pulverization using a bead mill by adjusting it to a specific range (6.5 to 9) with dispersion media containing substances like linear alkylbenzene sulfonic acid sodium salts, monoalkyl phosphates, sodium lauryl sulfate, cellulose polymers, and vinyl polymers, thereby reducing impurities from beads and mill components.

Benefits of technology

This approach significantly reduces impurities to less than 50 ppm, minimizing contamination and maintaining the purity of the refined particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602997000001
    Figure 0007602997000001
  • Figure 0007602997000002
    Figure 0007602997000002
  • Figure 0007602997000003
    Figure 0007602997000003
Patent Text Reader

Abstract

A production method according to the present disclosure comprises a) a step of stirring, with a bead mill, a mixture comprising a material to be milled, beads, and a dispersion medium; and b) a step of adjusting the pH of the mixture. This method reduces the contamination caused by milling processes with a bead mill.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for micronizing solid particles using a bead mill, and to particles micronized by said method. [Background technology]

[0002] As a means for reducing the size of solid particles, wet grinding using a grinding device such as a bead mill is known. Wet grinding using a bead mill has a high particle grinding capacity and can reduce the size of particles to the submicron order.

[0003] A bead mill is a device that uses an agitator to agitate the grinding media (beads) in a grinding chamber, giving the beads a large amount of kinetic energy, and reduces particles to fine particles using the collision and shear forces of the beads. For this reason, in wet grinding using a bead mill, contamination of the product can occur due to wear of the grinding media (beads) and mill parts (agitator, etc.).

[0004] In particular, in fields such as high-purity raw materials for electronic components and pharmaceuticals, even small amounts of impurities can have adverse effects such as poor product performance and health hazards, so such contamination must be avoided.

[0005] Patent Document 1 describes that the stirring surface inside the stirrer is made smooth and continuous without seams or recesses, thereby preventing accumulation of contaminants on the stirring surface.

[0006] Patent Document 2 describes that fine particles of a drug can be produced with little contamination by grinding the drug in the presence of a grinding medium containing beads made of a polymer resin or coated with a polymer resin.

[0007] Patent Document 3 describes a method in which particles of a nonsteroidal anti-inflammatory drug (NSAID) are dispersed in a liquid dispersion medium and wet-milled in the presence of a hard milling medium under acidic conditions of pH 2 to 6 to produce particles with an average particle size of less than about 400 nm.

[0008] Non-Patent Document 1 describes that efficient mill grinding was achieved in the presence of sodium lauryl sulfate and polyvinylpyrrolidone in a dispersion medium. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] U.S. Patent No. 6,582,285 [Patent Document 2] JP 2003-175341 A [Patent Document 3] Special Publication No. 8-501073 [Non-patent literature]

[0010] [Non-Patent Document 1] Engineering of nano-crystalline drug suspensions(Archive ouverte HAL) Summary of the Invention [Problem to be solved by the invention]

[0011] The present disclosure aims to reduce contamination resulting from the grinding process using a bead mill. [Means for solving the problem]

[0012] The present inventors have investigated various factors that affect contamination in a grinding process using a bead mill and found that the pH of the slurry during grinding has a large effect. In other words, the present disclosure is based on the discovery that contamination caused by grinding can be reduced by controlling the pH of the slurry of the material to be ground during grinding using a bead mill.

[0013] This specification discloses the following: (1) A method for producing microparticles by a grinding process using a bead mill, comprising the steps of: a) stirring a mixture containing a material to be ground, beads, and a dispersion medium in a bead mill; and b) adjusting the pH of the mixture. A method for producing fine particles of a ground material, comprising: (2) The manufacturing method according to the above (1), wherein the dispersion medium contains one or more selected from the group consisting of sodium salt of linear alkylbenzenesulfonate, monoalkyl phosphate, sodium lauryl sulfate, cellulose-based polymers, and vinyl-based polymers. (3) The method according to (1) above, wherein the dispersion medium contains polyvinylpyrrolidone. (4) The method according to (1) above, wherein the dispersion medium contains sodium lauryl sulfate. (5) The method according to (1) above, wherein the dispersion medium contains polyvinylpyrrolidone and sodium lauryl sulfate. The method for producing according to any one of the above (1) to (5), wherein the step of adjusting the pH in (6)b) is a step of adjusting the pH by adding an acidic substance or a basic substance. (7) The method according to any one of (1) to (6) above, in which impurities resulting from the pulverization process are reduced compared to before the pH adjustment. (8) The method according to any one of (1) to (7) above, wherein the impurities are derived from beads and / or a bead mill; (9) The method according to any one of (1) to (8) above, wherein the amount of impurities is less than 50 ppm based on the weight of the ground material before grinding; (10) The method according to any one of the above (1) to (9), wherein the beads are zirconia beads; (11) The method according to any one of the above (1) to (10), wherein the beads contain zirconium, yttrium and aluminum; (12) The method according to any one of (1) to (11) above, wherein the impurity is at least one selected from the group consisting of zirconium, yttrium, and aluminum; (13) The method according to any one of the above (1) to (12), wherein the step b) is a step of adjusting the pH of the mixture to 6.5 to 9; (14) A method for producing fine particles of a material to be ground by a grinding process using a bead mill, comprising mixing the material to be ground, beads and a dispersion medium, stirring the mixture having a pH of 6.5 to 9, and the amount of impurities is less than 50 ppm based on the weight of the material to be ground; (15) The method according to any one of (1) to (14) above, wherein the fine particles are microparticles; (16) The method according to any one of (1) to (14) above, wherein the fine particles are nanoparticles; (17) The method according to any one of (1) to (16) above, wherein the material to be ground is a pharmaceutical compound; (18) Microparticles obtained by the production method according to any one of (1) to (17) above; (19) The microparticle according to (18), which is a microparticle; (20) The microparticle according to (18) above, which is a nanoparticle; (21) The microparticle according to any one of (18) to (20) above, which comprises a pharmaceutical compound; (22) Fine particles according to any one of the above (18) to (21), in which the amount of one or more impurities selected from the group consisting of zirconium, yttrium, and aluminum is 0.0001 ppm or more and less than 50 ppm; (23) A pharmaceutical composition comprising the fine particles according to any one of (17) to (22) above; (24) A method for reducing impurities resulting from a grinding process using a bead mill, comprising the steps of: a) stirring a mixture containing the material to be ground, beads and a dispersion medium; and b) adjusting the pH of the mixture. A method comprising: (25) A method for reducing impurities resulting from a grinding process using a bead mill, comprising the steps of: a) mixing the material to be ground, beads and a dispersion medium; b) adjusting the pH of the mixture obtained in a); and c) agitating the mixture in a bead mill a method comprising: (26) The method according to (25) above, wherein the step b) is a step of adjusting the pH of the mixture obtained in the step a) to 6.5 to 9; and (27) The method according to (25) or (26) above, wherein the amount of impurities is 0.0001 ppm or more and less than 50 ppm based on the weight of the ground material before grinding. Effect of the Invention

[0014] The method of the present disclosure can reduce contamination caused by the grinding process in a bead mill. [Brief description of the drawings]

[0015] [Figure 1] This shows the contamination of beads in the microparticle sample obtained in Example 1. The horizontal axis shows the pH of the slurry subjected to the pulverization treatment. The vertical axis shows the amount (ppm / API: weight ppm relative to the drug microparticles) of elements (total of zirconium (Zr), yttrium (Y) and aluminum (Al)) derived from beads in the sample. [Diagram 2] This shows the effect of pH on the dissolution of bead components in Test Example 1. The horizontal axis shows the immersion time. The vertical axis shows the amount of elements (zirconium (Zr), yttrium (Y), and aluminum (Al)) derived from the beads in the sample. [Diagram 3] 1 shows the effect of pH on the grinding efficiency in Test Example 2. The horizontal axis shows the grinding time. The vertical axis shows the particle size (D50) of the drug microparticles after grinding. [Figure 4] This shows the effect of pH on contamination in Test Example 3. The horizontal axis shows the time of the grinding treatment. The vertical axis shows the amount of elements (zirconium (Zr), yttrium (Y), and aluminum (Al)) derived from the beads in the sample. [Diagram 5] This shows the effect of the grinding treatment and pH on contamination in Test Example 4. The horizontal axis shows the grinding treatment time. The vertical axis shows the amount of elements (zirconium (Zr), yttrium (Y), and aluminum (Al)) derived from the beads in the sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] In one aspect of the present disclosure, a method for producing microparticles by a grinding process using a bead mill is provided.

[0017] The term "microparticles" (also referred to herein as "micronized particles") as used herein means solid particles having an average particle size of 1000 μm or less obtained by a grinding technique using a bead mill (also referred to herein as a "grinding process"), and may have any shape, not limited to spherical.

[0018] In this specification, the average particle size of a particle is defined as the volume-based median diameter (D 50 The median diameter is indicated by the mean square root of the mean diameter of the particles. Those skilled in the art can measure the median diameter using routine methods.

[0019] The term "microparticles" as used herein refers to the above-mentioned fine particles having an average particle size on the order of microns, and refers to fine particles having an average particle size in the ranges of, for example, about 1 μm to about 1000 μm, about 1 μm to about 100 μm, about 1 μm to about 10 μm, about 10 μm to about 1000 μm, about 10 μm to about 50 μm, about 50 μm to about 100 μm, about 1 μm to about 50 μm, about 1 μm to about 30 μm, and about 1 μm to about 10 μm.

[0020] The term "nanoparticles" as used herein refers to the above-mentioned fine particles having an average particle size of the nano-order, for example, fine particles having an average particle size in the range of about 1 nm to about 1000 nm, for example, about 1 nm to about 100 nm, about 1 nm to about 10 nm, about 10 nm to about 1000 nm, about 100 nm to about 1000 nm, about 10 nm to about 50 nm, about 50 nm to about 100 nm, about 1 nm to about 50 nm, about 1 nm to about 30 nm, or about 1 nm to about 10 nm.

[0021] The term "ground material" as used herein means a solid material to be pulverized by the pulverization process of the present disclosure, and is usually a powder of a solid material. The particle size of the ground material before pulverization is not particularly limited as long as it can be pulverized to nanoparticles or microparticles by a bead mill. The particle size of the ground material that can be pulverized by the pulverization process of the present disclosure is, for example, in the range of 1 μm to 100 μm, 1 μm to 75 μm, 1 μm to 50 μm, 1 μm to 25 μm, 1 μm to 10 μm, and 1 μm to 5 μm.

[0022] The material to be ground used in the grinding process of the present disclosure may be any solid substance used in various fields, such as electronic component materials such as dielectrics, piezoelectrics, and magnetic materials, phosphors, battery electrode materials, pigments, paints, fine ceramic raw materials, abrasives, pharmaceuticals, pesticides, and powdered foods. For example, the material to be ground used in the pharmaceutical field may be a pharmaceutical compound that is an active ingredient of a pharmaceutical, and may be crystalline or non-crystalline. The material to be ground must be insoluble or poorly soluble in water, since it is wet ground.

[0023] In one embodiment, the milling process of the present disclosure comprises: a) stirring a mixture containing the material to be ground, beads and a dispersion medium; and b) adjusting the pH of the mixture. The present invention relates to a method for producing a semiconductor device comprising the steps of:

[0024] The beads used in the milling process of the present disclosure are not particularly limited as long as they are typically used in milling techniques using bead mills. A person skilled in the art can appropriately select the material and particle size of the beads taking into consideration various factors such as the specifications of the bead mill, the characteristics of the material to be ground (e.g., particle hardness, density, particle size, etc.), the desired particle size of the microparticles after grinding, and the viscosity of the slurry. Materials used in bead mills include, but are not limited to, glass, alumina, zircon (zirconia-silica ceramics), zirconia, steel, etc. Zirconia is particularly preferred as a bead material because it has high hardness and tends to be less likely to be mixed with debris due to bead deterioration. The particle size of the beads may be in the range of, for example, 0.03 mm to 1.0 mm, 0.1 mm to 1.0 mm, 0.1 mm to 0.8 mm, or 0.1 mm to 0.5 mm, but is not limited to these.

[0025] The dispersion medium used in the grinding process of the present disclosure is not particularly limited as long as it is a liquid medium in which the material to be ground is essentially insoluble, and those skilled in the art can select it appropriately according to the properties of the material to be ground.For example, water or various organic solvents (for example, alcohols such as methanol, ethanol, isopropanol, butanol, ketones such as acetone, methyl ethyl ketone, methyl propyl ketone, methyl isobutyl ketone, ethers such as isopropyl ether, methyl cellosolve, glycol esters such as ethylene glycol, propylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, esters such as ethyl acetate, halogenated hydrocarbons such as methylene chloride and trichloroethane, non-aromatic hydrocarbons such as cyclohexane, aromatic hydrocarbons such as toluene, linear hydrocarbons such as normal hexane, etc.) can be mentioned.

[0026] The amount of dispersion medium is not particularly limited as long as it is an amount that can sufficiently disperse the material to be ground and obtain a slurry of appropriate viscosity during the grinding process in a bead mill, and a person skilled in the art can select an appropriate amount depending on the properties of the material to be ground and the dispersion medium.

[0027] The mixture in step a) above can be stirred according to a procedure customary in the grinding technology using a bead mill, i.e., the mixture is stirred by an agitator in the stirring chamber of the bead mill under appropriately set operating conditions of the bead mill.

[0028] The pH adjustment in the above step b) may be performed after step a) or before step a). The pH adjustment before step a) may be performed, for example, in the following cases: 1) the pH of the slurry in which the material to be ground is dispersed in a dispersion medium is adjusted, and then beads are added to obtain the mixture in the above step a); or 2) beads are added to the dispersion medium, and then the pH of the slurry in which the material to be ground is dispersed in the dispersion medium is adjusted to obtain the mixture in the above step a). The pH adjustment can be performed by adding an acidic substance, a basic substance, or a neutral substance, particularly an acidic substance or a basic substance. For example, the pH can be adjusted by adding an acidic, basic, or neutral solution, particularly an acidic or basic solution, and the solution may be buffered or not. That is, by adding the above solution to a dispersion medium with a pH on the acidic side or a dispersion medium with a pH on the basic side, the pH can be adjusted to a level at which metal foreign matter is reduced, and the metal foreign matter can be reduced. Here, the acidic substance is a substance that dissolves in water, ionizes, and becomes hydrogen ions (H + ), and in a broader sense, it is a substance that donates hydrogen ions to other substances. A basic substance is one that dissolves in water and ionizes to give hydroxide ions (OH - ) refers to a compound having a hydroxyl group, and in a broad sense, is a substance that accepts hydrogen ions. Examples of solutions used to adjust the pH of the present disclosure include, but are not limited to, an aqueous acetic acid solution, an aqueous hydrochloric acid solution, a citrate buffer solution, a carbonate buffer solution, an aqueous phosphate buffer solution, an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous calcium hydroxide solution, and an aqueous ammonia solution. Those skilled in the art can appropriately select the type of solution used to adjust the pH, as well as its pH, concentration, and amount used, taking into consideration various factors such as the target pH, the material to be ground, the dispersion medium, and the properties of other components contained in the slurry.

[0029] In one embodiment using zirconia beads, in the above step b), the pH can be adjusted to a range of 6 to 9, for example, a range of 6 to 8.5, a range of 6 to 8, a range of 6.5 to 9, a range of 6.5 to 8.5, a range of 6.5 to 8, a range of 7.5 to 9, a range of 7.5 to 8.5, or a range of 7.5 to 8.

[0030] The grinding process of the present disclosure can be carried out using a commercially available bead mill device. The specifications and type of the bead mill device to be used are not particularly limited. The shape of the agitator provided in the bead mill device is also not limited, and may be, for example, a disk type, a pin type, a single rotor type, or the like. The grinding chamber may be of any type, such as a vertical type or a horizontal type. In addition, the operation method of the bead mill is also not limited, and may be, for example, a circulation type, a pass type, a batch type, or the like.

[0031] The amount of beads to be used can be appropriately selected by those skilled in the art, taking into consideration various factors such as the specifications of the bead mill (for example, the capacity of the grinding chamber), operating conditions, and the viscosity of the slurry.

[0032] The total amount of the mixture containing the material to be ground, beads, and dispersion medium to be fed into the bead mill can be appropriately selected by a person skilled in the art depending on the specifications of the bead mill (e.g., the capacity of the grinding chamber) and operating conditions, etc. In general, the volume ratio of beads to the capacity of the grinding chamber can be appropriately set within the range of 10 to 90%, and can also be set within the range of, for example, 25 to 90%, 50 to 90%, or 60 to 90%.

[0033] The operating conditions of the bead mill apparatus, such as the peripheral speed of the agitator, the mill cooling temperature, the residence time (processing time), etc., can be appropriately set according to the specifications of the bead mill apparatus used, following conventional procedures, taking into consideration various factors (the properties of the material to be ground, the type of dispersion medium, the viscosity of the slurry, the filling rate of the beads in the mill, the type of beads, the particle size of the microparticles obtained after grinding, the grinding efficiency, etc.).

[0034] In the grinding process of the present disclosure, additives can be added to the slurry as necessary. For example, a dispersant can be added to the slurry to improve the dispersibility of the material to be ground in the slurry, prevent aggregation, or stabilize the dispersion state.

[0035] The dispersant can be appropriately selected in consideration of various factors such as the properties of the material to be ground and the dispersion medium, the specifications and operating conditions of the bead mill, etc. Examples of the dispersant include surfactants such as carboxylates (fatty acid salts, etc.), sulfonates (linear alkylbenzenesulfonate sodium, etc.), phosphates (monoalkyl phosphates, etc.), and sulfates (sodium lauryl sulfate, etc.), and polymer compounds such as hydroxypropyl cellulose (HPC), hypromellose (hydroxypropylmethylcellulose (HPMC)), methylcellulose (MC), and polyvinylpyrrolidone (PVP), particularly water-soluble polymer compounds. Sodium lauryl sulfate and polyvinylpyrrolidone are preferred. The amount of the dispersant can be appropriately selected by a person skilled in the art according to conventional procedures. When the dispersant is a surfactant, the amount is, for example, 0.01 to 10.0% by weight, preferably 0.05 to 7.5% by weight, and more preferably 0.1 to 5.0% by weight, based on the total amount of the slurry. When the dispersant is a polymer compound, the amount is, for example, 0.1 to 20% by weight, based on the total amount of the slurry. . 0% by weight, preferably 0.25-15.0% by weight, more preferably 0.5-10.0% by weight. If these dispersants are not blended in the dispersion medium, the material to be ground may not disperse in the dispersion medium, or the grinding efficiency may decrease. When the dispersant and / or the polymer compound is dissolved or suspended in the dispersion medium, the pH of the dispersion medium may be such that the amount of metal foreign matter cannot be reduced. In this case, the pH can be adjusted to a level that reduces the amount of metal foreign matter by using a solution used for adjusting the pH, i.e., an aqueous solution of acetic acid, an aqueous solution of hydrochloric acid, a citrate buffer, a carbonate buffer, an aqueous solution of phosphate buffer, an aqueous solution of sodium hydroxide, an aqueous solution of potassium hydroxide, an aqueous solution of calcium hydroxide, an aqueous solution of ammonia, or the like.

[0036] The particles refined by the milling process of the present disclosure are separated from the beads by a separator in the bead mill, and then discharged from the bead mill as a slurry containing fine particles. The specifications and type of the separator are as follows: use The amount of the bead mill used varies depending on the type of bead mill used, and is not particularly limited.

[0037] The slurry discharged from the bead mill may be a composition in the form of a slurry containing fine particles, or the slurry may be dried according to a conventional procedure in the art to remove the dispersion medium and form a powder containing fine particles.

[0038] The term "contamination" as used herein refers to the mixing of impurities from the components of the bead mill (e.g., the stirring chamber, the agitator, etc.) or the materials that make up the beads during the grinding process using the bead mill. Such impurities are due to wear of the bead mill components and beads during the grinding process.

[0039] In one embodiment, the amount of impurities mixed in due to contamination resulting from the grinding process of the present disclosure is, for example, 0.0001 ppm or more and less than 50 ppm, 0.0001 ppm or more and less than 40 ppm, 0.0001 ppm or more and less than 30 ppm, 0.0001 ppm or more and less than 20 ppm, or 0.0001 ppm or more and less than 10 ppm, based on the weight of the obtained microparticles.

[0040] In one embodiment, the impurities resulting from the milling process of the present disclosure are components derived from the beads. In one embodiment in which the beads are zirconia beads, the impurities are one or more of the constituents of the zirconia beads (eg, zirconium, yttrium, and aluminum).

[0041] In one embodiment, impurities resulting from the milling process of the present disclosure are components derived from the materials that make up the bead mill, including components of stainless steel such as iron, molybdenum, chromium and nickel.

[0042] In a further aspect of the present disclosure, there is provided a microparticle obtainable by the method of the present disclosure. In one embodiment, the microparticles of the present disclosure are microparticles. In a further embodiment, the microparticles of the present disclosure are nanoparticles. In one embodiment, the microparticles of the present disclosure are nanoparticles comprising a pharmaceutical compound.

[0043] The form of the microparticles obtained by the method of the present disclosure is not particularly limited, and may be a composition in the form of a slurry obtained after the pulverization process of the present disclosure, or may be a composition produced by mixing the composition in the form of a slurry with additives, or may be a composition produced by drying and powdering the obtained slurry. In addition, the removal of foreign matter such as beads may be performed by filtering the slurry with a fine wet sieve to remove foreign matter, or by centrifuging the slurry to separate and remove metal foreign matter (bead contamination).

[0044] In a further aspect of the present disclosure, there is provided a composition or material comprising the microparticles obtained by the method of the present disclosure. Examples of such compositions or materials include electronic component materials such as dielectrics, piezoelectrics, and magnetic materials, phosphors, battery electrode materials, pigments, paints, fine ceramic raw materials, abrasives, pharmaceuticals, agricultural chemicals, powdered foods, and the like.

[0045] In a further aspect of the present disclosure, there is provided a pharmaceutical composition comprising the microparticles obtainable by the method of the present disclosure.

[0046] The pharmaceutical composition of the present disclosure can be obtained as a final product by using the microparticles obtained by the method of the present disclosure and undergoing several steps (e.g., granulation, sizing, tableting, coating, etc.) commonly used in the field of pharmaceutical formulations, as appropriate for the desired dosage form.

[0047] The following examples further illustrate the present disclosure and should not be construed as limiting its scope in any way. EXAMPLES

[0048] Example 1 7.5g (5w / w%) of phenytoin (Shizuoka Caffeine Industry) as a drug, 4.5g (3w / w%) of polyvinylpyrrolidone (PVP K-25, BASF Japan) as a polymer, and 0.375g (0.25w / w%) of sodium lauryl sulfate (Cognis Japan) as a surfactant were dispersed in 137.6g of purified water to make a slurry. The pH of this slurry was 3.88. The pH was adjusted by adding 1N sodium hydroxide aqueous solution to this slurry, and samples of various pH values ​​(pH 6.07, 6.68, 7.36, 8.14, 8.96, 10.37) were prepared. Each sample (100 g) and beads (217.3 g, packing rate 70%) were placed in a Dyno Mill Research Lab (WAB) and milled for 120 minutes using a bead mill (disk circumferential speed: 4 m / s, product temperature: 20°C, liquid speed: 45 g / min). The beads used in the milling process were YTZ balls (particle size 0.5 mm, zirconia beads manufactured by Nikkato). Here, the packing rate refers to the ratio of the true volume of the beads (percentage relative to the bulk volume), and the same applies below. The drug particle size after crushing is 1 μm or less (D 50 The particle size was measured using a Microtrac UPA 150 M (Microtrac Bell Corporation). Measurement conditions: Particle refractive index: 1.61 Set Zero: 60 seconds Measurement time: 60 seconds Number of measurements: 2 Shape: Non-spherical Solvent refractive index: 1.333 0.5 g of the sample after the pulverization process was weighed into a metal-free container, and an internal standard (Co) was added, followed by the addition of a NMP / HCl / HNO3 mixture (90:5:5), and the mixture was dissolved by ultrasonic irradiation to obtain a sample solution. The amount (ppm by weight / API) of bead components (zirconium, yttrium, and aluminum) relative to the drug in the sample was measured using an inductively coupled plasma mass spectrometry (ICP-MS) device (iCAPQ™, Thermo Fisher). Measurement conditions: Measured elements: Zr (m / z=90), Y (m / z=89), Al (m / z=27) Nebulizer: Coaxial nebulizer Spray chamber: Cyclone type Spray chamber temperature: constant temperature around 3℃ Injector inner diameter: 1.0mm Sample introduction method: Natural suction High frequency power: 1550W Cooling gas flow rate: 14L / min Auxiliary gas flow rate: 0.8L / min Measurement mode: KED Collision gas: Helium Additive gas: Oxygen Peristaltic pump speed: 20 rpm Integration time: 0.1 seconds Number of times: 3 The results are shown in Figure 1. As shown in Figure 1, when the slurry was adjusted to a pH of 6.68 to 8.14 and the grinding treatment was performed, contamination with bead components (zirconium, yttrium, and aluminum) was significantly reduced.

[0049] Test Example 1: Effect of pH on the dissolution of bead components 2.5g (5w / w%) of phenytoin (Shizuoka Caffeine Industry) as a drug, 1.5g (3w / w%) of polyvinylpyrrolidone (PVP K-25, BASF Japan) as a polymer, and 0.125g (0.25w / w%) of sodium lauryl sulfate (Cognis Japan) as a surfactant were dispersed in 45.88g of purified water to make a slurry. The pH of this slurry was measured to be 3.88. 1N NaOH was added to this slurry (45mL) to adjust the pH to 6.17. YTZ balls (0.925 g, YTZ-0.5, manufactured by Nikkato Corporation, diameter 0.5 mm) were weighed into a Falcon tube, and the slurry (5 mL) was added and allowed to stand at 25° C. As a control, the above slurry (pH 3.88) was used without adjusting the pH. After immersion for a predetermined period of time (1440 minutes, 2880 minutes), the supernatant was collected, and the amounts of zirconium, yttrium, and aluminum (wt ppm / API) were measured using an inductively coupled plasma mass spectrometer (iCAPQ (trademark), Thermo Fisher Scientific) in the same manner as described in Example 1. The results are shown in Figure 2. As shown in Figure 2, the elution of bead components was reduced by adjusting the pH of the slurry.

[0050] Test Example 2: Effect of pH on grinding efficiency The pH of the slurry (pH 3.88) prepared in Test Example 1 was adjusted with a 1N aqueous sodium hydroxide solution to prepare slurries with various pH values ​​(pH 6.68, 7.36, and 8.14). As a control, the slurry (pH 3.88) prepared in Test Example 1 was used as is without adjusting the pH. Each slurry (100 g) and beads (217.3 g, packing rate 70%) were charged into a Dyno Mill Research Lab (manufactured by WAB) and crushed by a bead mill. The beads used for the crushing process were YTZ balls (particle size 0.5 mm, zirconia beads manufactured by Nikkato). Sampling was performed at a predetermined time point during the grinding process, and the particle size of the drug particles in the sample was measured in the same manner as described in Example 1. 50 The values ​​were calculated, and the results are shown in Figure 3. As shown in FIG. 3, no significant effect of pH on the grinding efficiency was observed.

[0051] Test Example 3: Effect of pH on contamination The slurries with various pH values ​​(pH 3.88, 6.68, 7.36, and 8.14) prepared in Test Example 2 were each subjected to a bead mill pulverization process as described in Test Example 2, and samples were taken at predetermined times during the pulverization process. Each sample was dissolved as described in Example 1, and the amounts of zirconium, yttrium, and aluminum in the sample were measured using an inductively coupled plasma mass spectrometer. The results are shown in FIG. 4. As shown in FIG. 4, when the slurry was adjusted to a pH of 6.68 to 8.14 and the grinding process was performed, contamination by each bead component (zirconium, yttrium, aluminum) was reduced.

[0052] Test example 4: 100 g of the slurry (pH 3.88 and pH 7.36) prepared in Test Example 2 and 217.3 g (filling rate 70%) of YTZ balls (zirconia beads manufactured by Nikkato Corporation) were charged into a Dyno Mill Research Lab (manufactured by WAB Corporation) and either subjected to a grinding process using a bead mill (disk peripheral speed 4 m / s) or allowed to stand without grinding (disk peripheral speed 0 m / s). During the grinding process using the bead mill, samples were taken at predetermined time points, and the samples after grinding were dissolved and treated as described in Example 1. The amounts of zirconium, yttrium, and aluminum in the samples were measured using an inductively coupled plasma mass spectrometer. The results are shown in Figure 5. As shown in Figure 5, contamination by bead components increased when grinding was performed (disk peripheral speed 4 m / s). This is thought to be due to wear of the grinding media (beads) during the grinding process. In addition, contamination caused by the grinding process decreased when the pH of the slurry was adjusted (pH 7.36).

Claims

[Claim 1] A method for reducing impurities derived from zirconia beads resulting from a grinding process using a bead mill, comprising the steps of: Step a) preparing a slurry containing a material to be ground and a dispersion medium; Step b) adjusting the pH of the slurry obtained in step a) to 6.5 to 9; and Step c) A step of stirring the mixture containing the slurry obtained in step b) and zirconia beads in a bead mill. Contains or Step a') preparing a slurry containing a material to be ground, zirconia beads and a dispersion medium; Step b') adjusting the pH of the slurry obtained in step a') to 6.5 to 9; and Step c') A step of stirring the mixture obtained in step b') in a bead mill. The method includes:

Citation Information

Patent Citations

  • Production of formed amorphous silica

    JP1993294610A

  • surface modified nsaid nanoparticles

    JP1996501073A

  • Method for manufacturing particles of diagnostic image forming agent and drug

    JP2003175341A

  • Method for producing particulate silica slurry for cement composition, and particulate silica slurry for the cement composition

    JP2007070133A

  • Apparatus for sanitary wet milling

    US6582285B2